Morphological Characteristics of Bipolaris sorokiniana Causing Spot Blotch of Wheat and its In Vitro Management Using Different Botanicals - Pandey, Hemanta Kumar; Adhikari, Pratistha (Agriculture Development Journal, 2025)
Spot blotch disease of wheat caused by Bipolaris sorokiniana is one of the most concerning diseases of wheat, significantly constraining production over the last four decades. An estimated 25 million hectares of wheat grain are affected by spot blotch, particularly in humid and high temperature regions. The study was conducted at Agriculture and Forestry University, Rampur, Chitwan, in 2023 with the objective to characterize the morphological traits of B. sorokiniana and manage the disease using botanicals under laboratory conditions. The research included a field survey of ten locations in Chitwan to identify the severity of spot blotch disease using double digit scoring, morphological variations of B. sorokiniana conidia isolated from those locations, and in vitro management of the pathogen using botanical extracts (at 15 % concentration). The study revealed that the disease was most severe at Bijaynagar, Bharatpur-16, which recorded the highest number of spots per leaf (23) and the largest spot area (0.170 cm2). Isolate of B. sorokiniana from Bijaynagar has highest radial mycelium growth (8.62 cm). Among nine botanical extracts, garlic clove and neem extract effectively inhibited pathogen mycelial growth by 63.22% and 61.15 %, respectively. The study helped to identify severely affected locations in the Chitwan district along with potential efficient management options of B. sorokiniana.